(x, y) → (- 3, 7)
Using the method of elimination. That is manipulate the equations so that the coefficients of one of the variables are equal then add/subtract to eliminate it and solve for the other variable.
-9x + 4y = 55 → (1)
-11x + 7y = 82 → (2)
eliminating the terms in x
multiply equation (1) by 11
-99x+ 44y = 605 → (3)
multiply equation (2) by (- 9)
99x - 63y = - 738 → (4)
add (3) and (4) to eliminate x
- 19y = - 133
divide both sides by (- 19)
y =
= 7
substitute y = 7 into (1)
- 9x + 28 = 55
- 9x = 55 - 28 = 27
x =
= - 3
solution to system = (- 3, 7)